Neutron reflectivity and small angle neutron scattering: An introduction and perspective on recent progress - Penfold, J; Thomas, R (Elsevier, 2014)
In recent years both neutron reflectivity, NR, and small angle neutron scattering, SANS, have been applied to the study of increasingly complex surface and interfacial properties. The methodology and advantages of using these neutron scattering techniques to probe surfaces and interfaces will be briefly outlined. Some recent examples of surfactant, polymer and polymer-surfactant adsorption at the air-water, liquid-solid, and liquid-liquid planar interfaces are highlighted. These are contrasted by some examples of the nature of adsorption on colloidal sol particles and emulsion droplets. © 2014 Elsevier Ltd.